Pengaruh Digital Banking dan Literasi Keuangan terhadap Kinerja Keuangan pada PT Bank Rakyat Indonesia (Persero) Tbk Periode Kuartal 2022 – 2024 - Meisya Ayu Novianti; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2026)
The advancement of digital technology has driven significant transformation in the banking sector, particularly in the development of digital banking services. PT Bank Rakyat Indonesia (Persero) Tbk, as the largest state-owned bank, has introduced the BRImo application to enhance service efficiency and outreach. This study aims to examine the impact of digital banking and financial literacy on BRI’s financial performance, using Return on Assets (ROA) and Operational Efficiency Ratio (BOPO) as performance indicators. The research adopts a quantitative approach utilizing secondary data from quarterly financial reports for the years 2022 to 2024 and national financial literacy indexes issued by OJK. Digital banking is measured through BRImo user count, transaction volume, and digital fee-based income. The data is analyzed using multiple linear regression with SPSS. The findings indicate that BRImo transaction volume significantly affects both ROA and BOPO. However, digital fee-based income and financial literacy have a negative influence on efficiency. These results underscore the importance of optimizing digital transaction quality and developing adaptive financial literacy strategies that align with customer needs.